Pengaruh Kualitas Pelayanan, Motivasi, dan Kepercayaan Anggota Terhadap Partisipasi Anggota Koperasi KPN Karpend di Kecamatan Padang Ganting - Dwi, Faiza Alivia; Jean Elikal Marna (Universitas Negeri Padang, 2025)
The purpose of this research is to examine the influence of service quality, member motivation, and member trust on member participation at the KPN Karpend Cooperative in the Padang Ganting Sub-district. The research applied a quantitive approach with a descriptive method. The population of this research comprised 74 members of the cooperative, while the sample size was determined as 63 respondents using random sampling technique based on the Krejcie and Morgan table with a 5% error rate. Primary data were gathered by distributing structured questionnaires employing a Likert scale measurement. Data analysis process involved descriptive statistics and multiple linear regression analysis supported by SPSS version 21. Prior to hypothesis testing, the classical assumption test was performed to ensure that the regression model met the required statistical assumptions. These findings indicate that improving service quality, increasing member motivation, and strengthening member trust play an important role in enhancing member participation in cooperatives.